VARIASI GEOMETRI DESAIN ELEKTROMAGNETIK GENERATOR PERMANEN MAGNET 12SLOT 8POLE 500 WATT MENGGUNAKAN SOFTWARE BERBASIS FINITE ELEMENT METHOD ( FEM ) - Jumiyatun, Jumiyatun; Solihah, Ratih Mar’atus; Hisbullah, Ahsanul; Mansur, Khairunnisa; Mahmudi, Irwan (Foristek, 2025)
One of the main components of wind power plants that can be developed is the Permanent Magnet Synchronous Generator (PMSG). In this research, PMSG design will be carried out using Finite element method software with Geometry Variations of Permanent Magnet Synchronous Generator with a combination of 12 8-pole slots which will then be modeled on Finite element method software. In one variation of this generator geometry has been successfully created with good efficiency. This model will argue for the specifications of variations 1, 2 and 3 and are analyzed by comparison test scenarios and loading with load R. The generator with a no-load test simulation produces between variations in variation 1 of 10.93 volts, variation 2 of 12.67 volts, variation 3 of 13.77 volts. When testing load with load resulted in an efficiency of variation 1 of 20.5%, variation 2 of 19.6%, and variation 3 of 33.4%.